Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

The affective turn: Theorizing the social - Clough, Patricia Ticineto; Halley, Jean (Duke University Press, 2007)
In the mid-1990s, scholars turned their attention toward the ways that ongoing political, economic, and cultural transformations were changing the realm of the social, specifically that aspect of it described by the notion of affect: pre-individual bodily forces, linked to autonomic responses, which augment or diminish a body’s capacity to act or engage with others. This “affective turn” and the new configurations of bodies, technology, and matter that it reveals, is the subject of this collection of essays. Scholars based in sociology, cultural studies, science studies, and women’s studies illuminate the movement in thought from a psychoanalytically informed criticism of subject identity, representation, and trauma to an engagement with information and affect; from a privileging of the organic body to an exploration of nonorganic life; and from the presumption of equilibrium-seeking closed systems to an engagement with the complexity of open systems under far-from-equilibrium conditions. Taken together, these essays suggest that attending to the affective turn is necessary to theorizing the social.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; corps; discipline; identités; périodes historiques; représentations; sciences humaines; sciences sociales; sociologie; thématiques; traumatismes; émotions

The fourth world: an indigenous perspective on feminism and aboriginal women's activism - Ouellette, Grace Josephine Mildred Wuttunee (Basics from Fernwood Publishing, 2002)
"This book is not about feminism. Rather, feminism is the basis of the discussion, an example of how understanding oppression must consider a number of barriers. Euro-Canadian feminists rarely address the circumstances that are unique to First Nations' women, instead working with the assumption that all women are a part of a similar struggle. Ouellette attempts to confront these barriers. Throughout interviews with a number of women, she highlights the following four questions. To what extent do Aboriginal women understand experience and articulate their oppression? To what extent do colonized women perceive racism as the source of their oppression? To what extent do Aboriginal women view male domination within their own Aboriginal societies as the source of the oppression? How do Aboriginal women articulate racism and gender oppression?The author argues that there will always be a dichotomy between European and Aboriginal thought. This book makes an important contribution toward a greater understanding of Aboriginal thought and an Aboriginal perspective on society. The Fourth World theory is an integrate part of the "Circle of Life" philosophy of Aboriginal people. In keeping with oral traditions, these teachings are passed on at gatherings and in private conversations. They compromise a distinctly Aboriginal worldview."
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones

L'invention de l'hétérosexualité - Katz, Jonathan (Grands classiques de l'érotologie moderne, 2001)
L'auteur retrace l'histoire du concept d'hétérosexualité. Il analyse les textes d'auteurs comme Freud, Richard von Krafft-Ebing, Michel Foucault, Betty Friedan ou Kate Millet. Il nous montre que la distinction homosexuel/hétérosexuel ne repose pas sur une nature immuable mais constitue une façon récente de classer et de juger la société. [SDM].
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; hétérosexualité; identité sexuelle; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sex1181; sex1183; sexologie; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; épistémologie